Self-medication of adults and children in Poland - results from outpatient health care physicians online questionnaire - Kłoda, Karolina; Babicki, Mateusz; Biesiada, Aleksander; Gałązka-Sobotka, Małgorzata; Kowalska-Bobko, Iwona; Mastalerz-Migas, Agnieszka (Frontiers in Pharmacology, 2024)
In Poland, the area of self-medication requires scientific and organizational evaluation. So far, no solutions sanctioning self-medication have been introduced. Therefore, the aim of this study was to recognize and analyze the practical experience of outpatient physicians regarding self-medication of their patients, as well as self-medication of children by their caregivers.This study enrolled 386 participants and used a Computer-Assisted Web Interview (CAWI) that was disseminated online from 4th of July 2023 to 23rd of August 2023. The survey was addressed to outpatient healthcare physicians working in Poland.In doctors' perspective the main three reasons for choosing self-medication in Poland were: taking advice from other people -family members or friends (59.1%), finding information regarding treatment online (52.9%) and ability to self-medicate in this kind of symptoms/disease (51.6%). Among adult patients, in 72.1% of cases, an independent decision to start antibiotic therapy was made. Such a decision occurred in 39.8% of pediatric patients. Children caregivers were more likely to visit the physician immediately with symptoms than in the case of adult patients (42.2% vs 22.1%, p<0.001).Self-medication in Poland requires educational and organizational support at various levels -both social (information campaigns, school education), the health care system (increasing the role of medical professionals, including pharmacists), and finally in the area of legislation. Two areas seem to be particularly alarming -the use of antibiotics by adults and children and the mental health of both populations.